Kajian Dampak Kenaikan Harga Avtur Terhadap Keuntungan Pendapatan Maskapai Penerbangan (Rute Jakarta-Yogyakarta) - Purnama, M Herry; Susanti, Susanti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
Assessment of tire Tariff Schedules Commercial Scheduled Air Transport Related to Fuel Price illcrease Aircraft illtematio1wl Ai1port Yogyakarta Adi Sucipto is to know haw the effect of rising prices of aviation fuel or aircraft fuel to air freight carrier rates, namely PT. Garuda llldonesia (Garuda Airlines), PT. Sun Lion (Lion Airlines), and PT. Metro Batavia (Batavia Airlines) for route Jakarta - Yogyakarta during the period January to September 2011. Assess111c11 t method used is descriptive quantitative method to calculate the total cost of airline travel route Jakarta - Yogyakarta with calculation components include (a) Type of aircraft and aircraft type, (b) Using the assumption of hvo load factor is 65% lower load factor and load factor is high 80%, (c) Using tire asswnption of hvo aviation fuel prices are the lowest aviation fuel jet fuel price range, - and the highest price of aviation fuel during the period January to September 2011, the average ticket price flight route Jakarta - Yogyakarta period from January to September 2011. 17re results of the assessment indicates there is a difference significant benefits from each airline operator, when associated with the load factor and the difference in price of aviation fuel.